Hepatoprotective potential of Phyllanthus muellarianus leaf extract: studies on hepatic, oxidative stress and inflammatory biomarkers - Taofeek O. Ajiboye; Fatimah M. Ahmad; Airat O. Daisi; Aminat A. Yahaya; Oluwayemisi B. Ibitoye; Hamdalat F. Muritala; Taofik O. Sunmonu (Taylor & Francis Group, 2017)
Context: Leaves of Phyllanthus muellarianus (Kuntze) Exell. (Euphorbiacea) are widely used in the management of liver disorders in Nigeria. However, no there is no scientific validation to support this use. Objective: Hepatoprotective effect of Phyllanthus muellarianus aqueous leaf extract was investigated in acetaminophen-induced liver injury mice. Materials and methods: Hepatoprotective effect of Phyllanthus muellarianus aqueous leaf extract was evaluated in acetaminophen-induced hepatic damage in Swiss albino mice using biomarkers of hepatocellular indices, oxidative stress, proinflammatory factors and lipid peroxidation. Mice received distilled water, 100, 200, or 400 mg/kg b.w of Phyllanthus muellarianus aqueous leaf extract, respectively, for seven days. Treatment groups were challenged with 300 mg/kg b.w of acetaminophen on the sixth day. Results: Oral administration of Phyllanthus muellarianus aqueous leaf extract significantly (p < 0.05) attenuates acetaminophen-mediated alterations in serum alkaline phosphatase, alanine aminotransferase, aspartate aminotransferase, albumin and total bilirubin by 76.56, 85.41, 89.39, 82.77 and 78.38%. Similarly, acetaminophen-mediated decrease in activities of superoxide dismutase, catalase, glutathione peroxidase, glutathione reductase and glucose 6-phosphate dehydrogenase were significantly attenuated in the liver of mice by 85.10, 80.81, 80.45, 76.23 and 95.22%, respectively. Increased levels of conjugated dienes, lipid hydroperoxides, malondialdehyde, protein carbonyl, fragmented DNA, tumor necrosis factor-α, interleukin-6 and -8 were significantly lowered by Phyllanthus muellarianus aqueous leaf extract. Conclusion: Overall, results of this study show that Phyllanthus muellarianus halted acetaminophen-mediated hepatotoxicity due to its capability to enhance antioxidant enzymes.